Normal course of events amongst Swedish soccer players: an 8-year follow-up study. Issue 2 (June 1990) - Ekstrand, J; Roos, H; Tropp, H
Abstract : In this study 180 male soccer players entered into a prospective study of injuries in 1980. They were examined again in 1988. The aim of the present study was to evaluate the course of events during their active period. The study was carried out using a questionnaire. The importance of major injuries was evaluated. Hospital records were scrutinized and 179 of 180 (99 per cent) were included in the evaluation.